Design of a Wayfinding Sign System and Creative Map for Jati Agro Tourism in South Lampung - Axcal Fathi Primananda; Muhammad Redintan Justin (IMAGIONARY, 2025)
A sign system is a collection of visual elements designed according to specific rules to assist navigation and convey information within a certain area. Its functions include identifying facilities, providing directions, issuing warnings, and regulating behavior. In a tourism context, an effective sign system plays a crucial role in directing visitor movement and offering comprehensive information about the site. At Jati Agro Tourism in South Lampung, the current visual information system lacks clarity and consistency, making it less effective in delivering messages to visitors. Therefore, a redesigned sign system integrated with a creative map was developed as a primary navigation tool. This design project applies a visual communication approach that prioritizes clarity, visual attractiveness, and consistency. The aim is to produce an informative and engaging system that enhances visitor comfort and overall experience. A structured and aesthetically designed sign system is expected to improve the quality of informational services at Jati Agro as both an educational and recreational tourism destination.